Diálogos : una oportunidad para la paz. (2013)
This article aims to present an analysis of peace processes that take place in Havana, Cuba, reflecting on the different aspects that are part of this country, to do this 10 important points are set when face today of the peace accords. While these points justify the dialogue as the most suitable for the realization of a permanent closure of the armed conflict between the FARC and the state process, especially considering the role of education as an indispensable tool in building a culture of peace.